Investigations into biological factors associated with variation in growth performance of broiler chicks. - Elvis-Chikwem, Chinwendu Lorrita (2025)
Compositional differences in high and low bodyweight chick groups in early life may provide useful insights into the underlying causes of variation in broiler chick growth performance. Due to the substantial improvement in broiler genetics, it is usually speculated that broilers kept under the same environment and diet management would have relatively comparable uniformity in bodyweight. However, studies have shown considerable variations in bodyweight (11-18% coefficient of variation) in broiler flocks. Thus, the present research study was designed to investigate the differences in the digestive organ weight, tissue mineral profile, behavioral activities and transcriptomic profile of broiler chicks categorized as low or high bodyweight in early weeks of life. The study utilized day old male Ross 308 broilers which were kept under common environmental and dietary management throughout the experimental period. Early life was studied as it is the most critical period in broiler chick growth and development, for this reason it may be speculated that any difference observed during this period may be influential in understanding the characteristics of broilers performing lower or higher than the target breed. This would thus narrow the search to design more precise interventions to optimise growth performance and uniformity in broiler production. The first trial evaluated the differences in the digestive organ weights, bone mineral concentration and ileal transcriptomic of chicks categorized as super performing (SP) and underperforming (UP) chicks in the first week of life. Results obtained indicated that the SP had significantly higher bone sodium, phosphorus and rubidium concentrations relative to the UP group, in contrast the UP had significantly higher bone cadmium, caesium and lead compared to the SP group. Interestingly, the UP group had higher relative gizzard weight compared to the SP group. It was also revealed in the study that the SP group had higher ileal expression of important cytokine (IL26), and chemokine (IL8L1) compared to the UP group. In summary, it was observed that chicks of the same breed and of common environmental and diet conditions exhibited considerable differences in digestive organ weights, tibial bone mineral concentrations and ileal gene expression. In the second trial, further evaluation was conducted to better understand the differences observed in the first trial. Chicks were kept for up to 21days before sample collection, the study evaluated further differences in bone characteristics, liver mineral profile, and gut parameters of broilers categorized as low and high bodyweight to gain more insights into the differences in bone morphometry, liver and bone mineral profiles, gut pH and gizzard fibre content of the two group of chicks. Results indicated that the low weight group had higher concentration of bone manganese and strontium, and significantly higher liver manganese, cadmium and caesium compared to the high weight group. The low weight also had an interestingly low gizzard pH which corresponds to the significantly higher gizzard neutral detergent fiber (NDF) observed in the group. In summary, the results showed that broilers of the same breed, which were kept under the same diet and environmental conditions were different in bodyweights, tibial measurements, tibial bone mineral concentrations, liver mineral concentration, gut pH and gizzard fiber content. The third trial was designed to evaluate the behavioral activity of the low, average, and high weight chick groups to confirm the speculations obtained in trial 2 about litter consumption due to the observed reduction in gizzard digesta pH and fiber content. The study characterised chicks based on the hatch weight into low weight, average weight, and high weight groups on day 0, chicks’ behavioural activities such feeding, litter eating was monitored on day 0 and day 7. Bone, liver, and gizzard digesta samples were collected for mineral profile analysis, and the weight of the crop and gizzard were also recorded. In summary, results revealed higher feeding tendency of the high weight group on day 0, which may have influenced the higher bone mineral concentrations (Ca, P and Zn) in the high weight group, resulting in better performance than the low weight group. Trial 4 was a 2 by 2 factorial arrangement that assessed D0 bodyweight (High versus low) and litter type (Hardwood versus softwood). Results revealed that litter type did influence chicks’ bodyweight, and led to downregulation of tight junction, solute carriers and antioxidant genes in the bursal of the experimental chicks. The results obtained from the research studies revealed some interesting physiological and transcriptional differences in broiler chicks of varying bodyweight in early weeks of life and may contribute to further research targeting improved uniformity in broiler production.